1983
DOI: 10.1121/1.388849
|View full text |Cite
|
Sign up to set email alerts
|

Sound propagation over Dickins Seamount in the Northeast Pacific Ocean

Abstract: The acoustic propagation losses between a 230-Hz cw source and a multi-hydrophone receiving system were measured over Dickins Seamount in the Northeast Pacific. The source was towed at depths of 18 and 184 m. The receiving system had hydrophones spaced in depth from 323 to 633 m. The measurements were made to a maximum range of 130 km with the receiver located at a range of 60 km from the seamount peak. The results show that the seamount cast an acoustic shadow over the receiver, increasing the propagation los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Since the effects of seamounts are complex and the efficiency of numerical methods is usually low, previous studies on the sound propagation of seamounts mostly used 2D or N×2D models. With the deepening of ocean acoustics research, the focus gradually shifted to research about the 3D sound propagation phenomena of seamounts [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the effects of seamounts are complex and the efficiency of numerical methods is usually low, previous studies on the sound propagation of seamounts mostly used 2D or N×2D models. With the deepening of ocean acoustics research, the focus gradually shifted to research about the 3D sound propagation phenomena of seamounts [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out near Dickins Seamount in the northeast Pacific Ocean in 1975 [4,5] using explosive shots and CW sources. The results showed that the TL increased up to about 15 dB because the deep refracted waves would be blocked by the seamount, and the shadowing loss behind seamount was an f 1/2 dependence at frequencies greater than 50 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment showed that the peak pressure levels recorded at Wake were as much as 35 dB below those at Midway and the spectral energy density ratio between Wake and Midway was frequently independent. Another experiment was carried out over the Dickins Seamount in the northeast Pacific ocean in 1975 [6,7] by using both explosive shots and CW sources. The results showed that the increased TL was up to 15 dB for the shallow source in which all deep refracted waves could be blocked by the seamount and the shadowing loss behind the seamount was an 𝑓 1/2 dependence at frequencies larger than 50 Hz.…”
mentioning
confidence: 99%
“…3, the BELL-HOP ray model [8] is used to calculate the propagation sound field for the environments with/without seamount. According to the principle of reciprocity, [7] the positions of source and receiver are exchanged in the calculation. The bottom parameters were measured through core sampling in the experiment.…”
mentioning
confidence: 99%
“…As for the seamount scattering, a series of research was done [3,4,5,6]. However, these articles did not have a viewpoint of the interrupting phases in the recorded wave trains at the SOFAR channel.…”
Section: Introductionmentioning
confidence: 99%